Critical Roles of Spätzle5 in Antimicrobial Peptide Production Against Escherichia coli in Tenebrio molitor Malpighian Tubules - Ali Mohammadie Kojour, Maryam; Edosa, Tariku Tesfaye; Jang, Ho Am; Keshavarz, Maryam; Jo, Yong Hun; Han, Yeon Soo (Frontiers in Immunology, 2021)
The dimeric cytokine ligand Spätzle (Spz) is responsible for Toll pathway activation and antimicrobial peptide (AMP) production upon pathogen challenge in Tenebrio molitor. Here, we indicated that TmSpz5 has a functional role in response to bacterial infections. We showed that the highest expression of TmSpz5 is induced by Candida albicans. However, TmSpz5 knockdown reduced larval survival against Escherichia coli and Staphylococcus aureus. To evaluate the molecular mechanism underlying the observed survival differences, the role of TmSpz5 in AMP production was examined by RNA interference and microbial injection. T. molitor AMPs that are active against Gram-negative and -positive bacteria, including Tmtenecins, Tmattacins, Tmcoleoptericins, Tmtaumatin-like-proteins, and Tmcecropin-2, were significantly downregulated by TmSpz-5 RNAi in the Malpighian tubules (MTs) following in challenge with E. coli and S. aureus. However, upon infection with C. albicans the mRNA levels of most AMPs in the dsTmSpz5-injected group were similar to those in the control groups. Likewise, the expression of the transcription factors NF-κB, TmDorX2, and TmRelish, were noticeably suppressed in the MTs of TmSpz5-silenced larvae. Moreover, E. coli-infected TmSpz5 knockdown larvae showed decreased antimicrobial activity in the MTs and hindgut compared with the control group. These results demonstrate that TmSpz5 has a defined role in T. molitor innate immunity by regulating AMP expression in MTs in response to E. coli.